ANALYSIS OF STUDENT ASSISTANCE IN MAKING EFLYER AND WEBINAR ACTIVITY CERTIFICATES USING CANVA APPLICATION AT CV TEMAN KOLABORASI ANDA DEPOK CITY - Sintesa, Nika; Harmaen, Harmaen; Indriany, Yuli; Irdiyansah, Iyan (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Webinars have been a popular activity since the beginning of the COVID-19 pandemic until now, especially for students and the general public who want to increase their knowledge and get a certificate as part of their portfolio. The promotion of webinars is done through e-flyers with various themes supported by the internship team under CV Teman Kolaborasi Anda. This research aims to analyze the assistance in making e-flyers and webinar certificates. The method used is descriptive qualitative with an explanatory approach, using secondary data in the form of e-flyers from social media such as Instagram, Facebook, WhatsApp, and email. The research subjects were trainees, namely university students, fresh graduates, and some high school students who participated in training on making e-flyers and webinar certificates using the Canva application at CV Teman Kolaborasi Anda, Depok City. The object of research is the assistance process in making e-flyers and webinar certificates using the Canva application. The results showed that some e-flyers did not meet the standards due to differences in design styles, while the certificates were in accordance with the specified standards by using standardized templates. Assistance was provided to ensure the existence of standardized design standards by utilizing the Canva application which provides various free templates. This activity was conducted online and guided by the Founder of CV Teman Kolaborasi Anda. This training equips the participants, who are apprentices, with practical skills in e-flyer and certificate design, thus improving their readiness to enter the workforce with a combination of soft and hard skills that are in line with industry needs.